KOLONIALE FREMDHEITSERFAHRUNG UND BIKULTURELLE EHESCHLIESSUNGEN: ZUR KOLONIALEN AMBIVALENZ BEI JESCO VON PUTTKAMER UND PIERRE LOTI - NKOUDA SOPGUI, Romuald Valentin (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Colonial experience of Strangeness and Bicultural Marriages: On Colonial Ambivalence in Jesco von Puttkamer and Pierre Loti. The following article goes into the literary analysis of colonial strangeness and bicultural marriages through two colonial texts. Jesco von Puttkamer and Pierre Loti exemplify the subject of colonial strangeness from a travel experience. In their texts, colonial experience of foreignness focuses on excerpt of the colonists from their familiar surroundings with travel. The journey in the sign of colonization goes hand in hand with the perception of the foreign space and its inhabitants. Puttkamer's and Loti's main characters do not however abide by the colonial rule of radical distancing from the natives because they have romantic relationships with black women. In both cases, it is an ambivalent attitude of the colonial masters towards the non-European foreign region, which oscillates between positive and negative stereotypes. The depictions of mixed marriages are also characterized by ambivalence, because the black woman acts both as an object of fascination or desire and as a subject of racial power differences. These statements justify the thesis of colonial ambivalence, which is the subject of discussion here. The authors thus confirm the following results, which the article concludes with; namely, that the line between exotic strangeness and colonial stereotyping is difficult to draw. The analyzed narrative sequences also provide information that colonial intermarriage leads to mutual transformations. As an exchange of bodies, colonial marriages illustrate the interweaving of the colonial periphery and the European metropolis. To achieve the above goals, Whiteness and (post)colonial Studies provide theoretical foundations that make my investigation more plausible. Article history: Received 30 June 2022; Revised 26 August 2022; Accepted 25 November 2022; Available online 20 December 2022; Available print 30 December 2022. REZUMAT. Experiența colonială de străinătate și căsătorii biculturale: despre ambivalența colonială la Jesco von Puttkamer și Pierre Loti. Articolul următor intră în analiza literară a străinătății coloniale și a căsătoriilor biculturale prin două texte coloniale. Jesco von Puttkamer și Pierre Loti exemplifică subiectul ciudățeniei coloniale dintr-o experiență de călătorie. În textele lor, experiența colonială a străinătății se concentrează pe fragmente ale coloniștilor din mediul lor familiar cu călătoriile. Călătoria în semnul colonizării merge mână în mână cu percepția spațiului străin și a locuitorilor acestuia. Personajele principale ale lui Puttkamer și Loti nu respectă totuși regula colonială a distanței radicale de nativi, deoarece au relații romantice cu femei de culoare. În ambele cazuri, este o atitudine ambivalentă a stăpânilor coloniali față de regiunea străină non-europeană, care oscilează între stereotipuri pozitive și negative. Reprezentările căsătoriilor mixte sunt, de asemenea, caracterizate de ambivalență, deoarece femeia de culoare acționează atât ca obiect al fascinației sau al dorinței, cât și ca subiect al diferențelor de putere rasială. Aceste afirmații justifică teza ambivalenței coloniale, care face obiectul discuției aici. Autorii confirmă astfel următoarele rezultate, cu care articolul se încheie; și anume că linia dintre ciudățenia exotică și stereotipurile coloniale este greu de tras. Secvențele narative analizate oferă, de asemenea, informații că căsătoriile coloniale duce la transformări reciproce. Ca schimb de corpuri, căsătoriile coloniale ilustrează împletirea periferiei coloniale cu metropola europeană. Pentru a atinge obiectivele de mai sus, Albul și Studiile (post)coloniale oferă baze teoretice care fac investigația mea mai plauzibilă. Cuvinte-cheie: călătorii coloniale, străinătate, ambivalență, căsătorii interculturale, reciprocitate